Impact of Procedural Sedation on the Clinical Outcome of Microelectrode Recording Guided Deep Brain Stimulation in Patients with Parkinson’s Disease - Bos, Michael J. (J Clin Med, 2021)
Background: Subthalamic nucleus (STN) deep brain stimulation (DBS) has become a routine treatment of advanced Parkinson’s disease (PD). DBS surgery is commonly performed under local anesthesia (LA) to obtain reliable microelectrode recordings. However, procedural sedation and/or analgesia (PSA) is often desirable to improve patient comfort. The impact of PSA in addition to LA on outcome is largely unknown. Therefore, we performed an observational study to assess the effect of PSA compared to LA alone during STN DBS surgery on outcome in PD patients. Methods: Seventy PD patients (22 under LA, 48 under LA + PSA) scheduled for STN DBS implantation were included. Dexmedetomidine, clonidine or remifentanil were used for PSA. The primary outcome was the change in Movement Disorders Society Unified Parkinson’s Disease Rating Score III (MDS-UPDRS III) and levodopa equivalent daily dosage (LEDD) between baseline, one month before surgery, and twelve months postoperatively. Secondary outcome measures were motor function during activities of daily living (MDS-UPDRS II), cognitive alterations and surgical adverse events. Postoperative assessment was conducted in “on” stimulation and “on” medication conditions. Results: At twelve months follow-up, UPDRS III and UPDRS II scores in “on” medication conditions were similar between the LA and PSA groups. The two groups showed a similar LEDD reduction and an equivalent decline in executive function measured by the Stroop Color-Word Test, Trail Making Test-B, and verbal fluency. The incidence of perioperative and postoperative adverse events was similar between groups. Conclusion: This study demonstrates that PSA during STN DBS implantation surgery in PD patients was not associated with differences in motor and non-motor outcome after twelve months compared with LA only.